(untitled) (Eurasian Journal of Technology and Innovation, 2026)
The paper defines the longitudinal and transverse stability of special vehicles and indicates the ways of lowering these angles. The modernization of special vehicles made it possible to lower the center of gravity of various special vehicles by an average of 450-100 = 550 mm. In the upgraded truck layout, 300+100=400 mm. On the upgraded experimental KAMAZ, the angle of lateral stability has decreased by 50C and the angle of static longitudinal stability has been reduced by an average of 80C, which these angles will allow to meet the requirements of the applicable standards.